2013
DOI: 10.2466/15.09.pr0.112.3.992-1004
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Anxiety and Dimensional Personality Model in College Students

Abstract: A sample of 402 volunteer male (n = 156) and female (n = 246) Kuwaiti undergraduates responded to the Arabic versions of the Kuwait University Anxiety Scale and the Eysenck Personality Questionnaire. The latter questionnaire has four subscales: Psychoticism, Extraversion, Neuroticism, and Lie. Women obtained a higher mean score on Kuwait University Anxiety Scale and Neuroticism than did men, while men had a higher mean score on Psychoticism than did women. Factor analysis of the intercorrelations between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…The hypotheses were confirmed in the second study. The sex differences were statistically significant for ASMH scores, physical health and happiness, with boys obtaining higher scores, consistent with previous studies on Arab adults (Abdel-Khalek, 2018) and consistent with the significantly high scores of Arab females for neuroticism and anxiety in previous research (Abdel-Khalek, 2013, 2019b.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The hypotheses were confirmed in the second study. The sex differences were statistically significant for ASMH scores, physical health and happiness, with boys obtaining higher scores, consistent with previous studies on Arab adults (Abdel-Khalek, 2018) and consistent with the significantly high scores of Arab females for neuroticism and anxiety in previous research (Abdel-Khalek, 2013, 2019b.…”
Section: Discussionsupporting
confidence: 91%
“…Boys obtained significantly higher mean scores than did their female counterparts on four of the five scales. Abdel-Khalek (2003, 2013, 2019b) reported higher mean scores of girls compared to boys in anxiety, depression and neuroticism, and this is consistent with the low scores of the girls on mental and physical health as well as life satisfaction. However, the higher mean score for boys on religiosity than the girls was not congruent with previous studies on adults (Miller, 2003, p. 49; Spilka et al, 2003; Sullins, 2006).…”
Section: Studysupporting
confidence: 73%
“…Extroversion and introversion were most clearly proposed by Carl Jung, who suggested that an extroverted person is energized by being outgoing and socially oriented, while an introvert person is quiet and reserved [ 41 ]. These ideas are considered as Jung’s most important contributions to the field of personality psychology, as almost all models of personality now include these concepts [ 42 , 43 ]. Extroversion and the hedonic value are similar in that they both take an approaching manner towards the environment; consistent adjectives for extroversion include active, assertive, energetic, enthusiastic, outgoing and talkative [ 35 ].…”
Section: The Similarity Between Eysenck’s Personality Dimension and E...mentioning
confidence: 99%
“…Emotional instability, which is the typical feature of neuroticism, is the personality trait most closely associated with mental health challenges [ 50 ]. It is associated with norepinephrine and the sympathetic nervous system, which regulate emotional arousal and control sympathetic autonomic responses [ 43 ]. Individual differences in emotional stability are thought to reflect the core of neuroticism.…”
Section: The Similarity Between Eysenck’s Personality Dimension and E...mentioning
confidence: 99%
See 1 more Smart Citation